AB0348 A Retrospective Review of Dispensing of Concomitant Glucocorticoids with Biologics Prescribed for The Treatment of Rheumatoid Arthritis in The Australian Population. (15th July 2016) - Jones, G.; Hall, S.; Littlejohn, G.; Chung, E.; Barrett, R.; Button, P.
Abstract : Background: The treatment of Rheumatoid arthritis (RA) in Australia is consistent with the current international guidelines of starting a biologic (b) DMARD in combination with methotrexate (MTX) where possible and/or other synthetic DMARDs with or without glucocorticoids (GCs). There is limited data available on the effects of various bDMARDs on oral GCs consumption in a real world data setting and in the same patient population. Objectives: The objective of the study was to investigate the usage of concomitant GCs with bDMARDs for the treatment of RA patients over time. Methods: Concessional (government subsidised) RA patients ≥18 years of age for whom bDMARDs were first dispensed for their RA (between 01August 2010 and 31July 2013), and who were in the Australian Medicare 10% sample database provided by the Department of Health and Aging through an Australian healthcare consulting company (PROSPECTION) were followed for a period of 2 years (until 31 July 2015). bDMARDs included: abatacept (IV and SC), adalimumab, certolizumab pegol, etanercept, golimumab, infliximab, and tocilizumab. Data were analysed using descriptive statistics for continuous variables and frequency counts for categorical variables. Individual anti-TNFs were equivalent in all analyses and therefore were combined for simplicity. Results: Data from 269 patients were analysed. Of the patients who received oral GCs at some point during the study period (86%; n=230), 49% were ≥65 years old and 51% were 18–64 years old. The majority (81%) were females. For all patients, median dose of oral GCs was 4.1 (min 0, max 21) mg/day at one year prior to initiation of a bDMARD, 2.9 (min 0, max 22.2) mg/day and 2.0 (min 0, max 17.3) mg/day at 1 and 2 years, respectively, post-bDMARDs initiation. Daily GCs doses across the analysis time points and by drug group are presented in Table 1 . Daily dose changes at 1–2 years post initiation of bDMARDs from 1 year before initiation of bDMARDs were statistically significant for all bDMARDs (p<0.0001), all anti-TNFs (p<0.0001) and tocilizumab (p=0.0002). Percentage of patients who stopped GCs at any time post initiation of a bDMARD was 43% for all RA bDMARDs, 44% for all anti-TNFs, 27% for abatacept and 39% for tocilizumab. 31 percent of patients who remained on biologics for the observation period in the "all RA bDMARDs" group had an increase in GCs dose and 60% had a decrease after 1-year and 65% after 2 years; percentage increase and decrease in GCs doses for all groups are listed in Table 2 . Conclusions: In the Australian setting, the majority of RA patients who were taking oral GCs had reductions in their daily GCs doses after initiation of bDMARDs; which continued for up to 2 years post treatment initiation. Acknowledgement: The study was sponsored by Roche Products Pty. Limited. Medical writing was provided by Dr Joseline Ojaimi from Roche. Disclosure of Interest: G. Jones: None declared, S. Hall: None declared, G. Littlejohn: None declared, E. Chung Consultant for: Roche Products, Pty. Ltd, R. Barrett Employee of: Roche Products, Pty. Ltd, P. Button Employee of: Roche Products, Pty. Ltd